Penguatan Nilai-Nilai Luhur Pancasila Dalam Al-Qur’an Kepada Peserta Didik Pada Layanan Bimbingan Konseling - Nasution, Toni; Hafizi, M. Zainul; Siregar, Hendri (LPPPI Publishing, 2024)
Counselors as teacher's guidance and counseling should provide reinforcement of the noble values ??of Pancasila in the Qur'an in teaching and learning activities so that students are able to control themselves as good and obedient students in the life of the nation and state. Pancasila sublime value is embedded as the foundation of the Indonesian people who are the spirit of the nation. Administratively, in the 1945 Constitution, Pancasila contains the values ??of national character education which play an important role as a spiritual dimension, a cultural dimension and an institutional dimension. For this reason, the noble values ??of the Pancasila should be practiced in life and lived rather not only as symbols. Often the slogan of the Pancasila noble values ??is a guideline for the life of the nation and state and a reflection of religion because Pancasila itself is contained in the Qur'an itself. Indeed, the precepts in Pancasila, accept things, which are also new to Muslims. Affirmation to the essence of God, humanity, unity, deliberation and justice is a terminology that is widely used in the Qur'an to be the goal of Islamic prescribed. The problem among the natives with the packaging of Pancasila is indigenous (non-Arabic) so that the taboo and blind people judge it as a value that comes from religion. In this case, this article will be discussed in depth and analytically so as to be able to open up the discourse of thinking about the noble values ??of the Pancasila itself contained in the Qur'an.